Korelasi Kadar Prokalsitonin (PCT) Dengan Rasio Neutrofil Limfosit (RNL) Pada Pasien COVID-19 - Apriliani, Isnawati; Fajrunni’mah, Rizana; Djajaningrat, Husjain; Widiantari, Aninda Dinar; Murtiani, Farida (RSUP Dr. Kariadi, 2023)
BACKGROUND: Covid-19 treatment should be done early before the disease progress. Inflammatory biomarker is needed to ascertain the severity of disease as soon as possible. Neutrophil-to-lymphocyte ratio (NLR) and Procalcitonin (PCT) are two of biomarker that are clinically used around the world. NLR is simpler, can routinely be done and available in peripheral region while PCT is more effective to describe inflammation. PURPOSE: This study aims to determine the correlation of procalcitonin (PCT) levels with neutrophil lymphocyte ratio (NLR) in COVID-19 patients. METHOD: This study is an analytic observational with a cross sectional design. We extracted data from medical record. Samples were 415 COVID-19 patients undergoing inpatient care at the Budhi Asih Hospital, East Jakarta for January - December 2021. RESULTS: Prevalence of male patients more than ≥60 years were 78 patients (18,8%) while female patients were 68 patients (16,4%). Average of PCT level was 1,93 ng/mL (0,02-200 ng/mL). Average of NLR was 5,09 cells/mm3 (0,22-31 cells/mm3). Spearman test proved there was a significant correlation between PCT and NLR levels in COVID-19 patients (p value = 0,0001). CONCLUSION: The higher the PCT level, the higher the NLR value in COVID-19 patients.